Peer-facilitation type, learning environment, anxiety level, and conceptual understanding in biology - Calipjo, Arleen M. (2006)
The effects of peer facilitation by a trained leader on students' perception of the learning environment, anxiety level, and conceptual understanding were investigated in this study. The study involved two second year biology classes of Victorious Christian Montesorri College in GMA Cavite. Pretest-posttest two-group design was employed. Learning Environment Scale, Anxiety scale, and Conceptual Understanding Test were the instruments developed by the researcher to gather data. Among the conclusions were: that peer facilitation with trained leader improves students' perception of the learning environment, that it lowers anxiety level, and effects better conceptual understanding.